SPATIAL AUTO CORRELATED ANALYSIS OF TUBERCULOSIS INCIDENTS IN PADANG CITY - Arlinda, Sari; -, Lindawati; MT, Mukhlis (Universitas Aisyah Pringsewu, 2025)
Introduction: Tuberculosis is a chronic infectious disease caused by the bacteria mycobacterium tuberculosis. TB cases in Indonesia are in second place with the largest number of TB sufferers in the world after India and West Sumatra is one of the provinces in Indonesia with the number of cases in 2020 as many as 14,398 cases based on the report of the Indonesian Ministry of Health. Tuberculosis (TB) has various risk factors. There are several factors that influence the incidence of TB, including environmental factors, external environment, socio-economic and behavior. Therefore, the purpose of this study is to determine the risk factors for the incidence of tuberculosis in Padang City. Methods: This study is an analytical observational study using a case control design by presenting data descriptively and spatially. The focus of this study is the analysis of spatial autocorrelation of tuberculosis incidence in Padang City from January to December 2024. Data collection was carried out by observation, interviews, and measuring air quality in selected sample houses. Results And Discussion: The results of the analysis found a positive autocorrelation between sanitation facilities factors and tuberculosis incidence (clustered pattern) and no autocorrelation between knowledge, behavior and environmental conditions factors and tuberculosis incidence. There are 5 sub-districts that are spatially significant between knowledge, behavior, sanitation facilities and environmental conditions, namely Padang Barat, Padang Timur, Kuranji, Bungus Teluk Kabung, and Lubuk Kilangan Sub-districts. Conclusion: Based on the results above, it can be concluded that there is autocorrelation between sanitation facilities and tuberculosis incidence and there is no autocorrelation between knowledge, behavior and environmental conditions. Therefore, it is expected that the community can implement a clean and healthy lifestyle and related agencies can re-inspect people's homes and educate people infected with tuberculosis.